Improving Students' Critical Thinking Skills Through STEMEC-Based e-LKPD Using Imagy Products - Sihaf, Ainun Nazah; Saminan*, Saminan; Susilawati, Susilawati; Sattar, Mohammad (Jurnal IPA & Pembelajaran IPA, 2025)
Students' critical thinking skills at school have not improved. This study aims to analyze the effectiveness of e-LKPD based on STEMEC (science, technology, engineering, mathematics, entrepreneurship, and character) in improving students' critical thinking, especially on Hooke's Law material, by utilizing the imagy tool. The research method used was an experiment with a one-group pretest-posttest design involving 34 grade XI students at SMAN 5 Banda Aceh. The results showed a significant increase in students' critical thinking after the learning intervention. The average pretest score of 38.82 increased to 80.44 on the posttest with an average N-Gain score of 0.677, indicating an increase of 67.7%. The majority of students 22 people are in the high improvement category, 9 people in the medium category, and 3 people in the low category. The STEMEC approach with imagy not only improves conceptual understanding, and critical thinking, but also helps students develop 21st century skills, including collaboration, communication, entrepreneurship and character skills. These findings prove that the implementation of STEMEC as a holistic and effective learning strategy can train students' mindset and character in improving their competence in the fields of science and technology.